2019
DOI: 10.1140/epjc/s10052-019-6818-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived triplinos and displaced lepton signals at the LHC

Abstract: We explore the possibility of having superpartners of triplet Higgs bosons, named as 'triplinos'. They form a part of light neutralinos and charginos in a Y = 0 extended supersymmetric Standard Model. For this model such electroweakinos do not have direct couplings to the Standard Model fermions. On top of that, due to very compressed spectrum for lighter neutralinos and charginos, their decay products coming from three body decays are very soft and thus can evade the current collider bounds. These decays are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…One common feature that the both scenarios posses is that due to very compressed spectrum the missing energy cancels between the two DM particles, one coming from the charged Higgs decay and the other produced in association. The similar behaviour is also observed in charged Higgs pair production and generic to compressed spectrum scenarios found in supersymmetry [102] and Universal Extra Dimensions [103]. Nevertheless, for the IDM scenario due to a mass gap around 5-10 GeV among the charged Higgs and other other Z 2 -odd neutral Higgs bosons, p T of the the leptons coming from the charged Higgs boson can be around 20 GeV considering the boost effect at 100 TeV centre of mass energy.…”
Section: Lhc Phenomenologysupporting
confidence: 76%
“…One common feature that the both scenarios posses is that due to very compressed spectrum the missing energy cancels between the two DM particles, one coming from the charged Higgs decay and the other produced in association. The similar behaviour is also observed in charged Higgs pair production and generic to compressed spectrum scenarios found in supersymmetry [102] and Universal Extra Dimensions [103]. Nevertheless, for the IDM scenario due to a mass gap around 5-10 GeV among the charged Higgs and other other Z 2 -odd neutral Higgs bosons, p T of the the leptons coming from the charged Higgs boson can be around 20 GeV considering the boost effect at 100 TeV centre of mass energy.…”
Section: Lhc Phenomenologysupporting
confidence: 76%
“…Finalstates of 4 , 3 + ≥ 1j, 2 + ≥ 2j are also studied as we found that MATHUSLA regions are preferred by BP2, BP3 for Y N = 5 × 10 −8 , 5 × 10 −9 , respectively. To complete the study we drew the regions plots in M N − M Z B−L (in Figure 12), M Z B−L − Y N (in Figure 13) and M N − Y N (in Figure 14) planes, where in Figure 13 The study performed in this article can be easily attributed to other U (1) models with righthanded neutrino [67][68][69][70] and other displaced neutral decays [71,72]. The segregation of transverse and longitudinal displaced decays manifests the longitudinal boost effect at higher centre of mass energies.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting scenarios appear when one considers the charged Higgs boson super-partner, i.e. the chargino, which can give rise to displaced decays [55]. The displaced Higgs boson decays can also appear in various SUSY scenarios [56,57].…”
Section: Long-lived Charged Statesmentioning
confidence: 99%

Obscure Higgs boson at Colliders

Bandyopadhyay,
Costantini
2020
Preprint
Self Cite